Speech outcome evaluation in post-cleft palate closure patients with two flaps pushback technique - Irma Kusumawati; Andri Hardianto; Agus Nurwiadh (Majalah Kedokteran Gigi Indonesia, 2022)
Speech quality is an essential output in assessing the success of a palatoplasty. The goal of a palatoplasty is not merely to create a simple anatomical closure of the palate, but also to create an adequate velopharyngeal mechanism for a normal speech outcome and to prevent abnormal maxillofacial development after surgery. The aim of this study is to find out the difference in speech outcome between post-cleft palate closure patients and patients without cleft palate. An analytical retrospective study was conducted on 22 children (n = 22) with complete unilateral cleft palate, who had been treated using two flap push back technic of palatoplasty during 2014-2017 by purposive sampling method, and 22 children without cleft palate as the control group. The evaluation of speech outcome was done using an assessment of perception by doing a speech pathologist and instrumental examination by taking a lateral cephalometry radiograph. The perception was assessed by the articulation pattern, hypernasality, and speech intelligibility. The lateral cephalometry radiograph was taken at /i/ phonation to measure the distance velum to the posterior pharynx wall. Data were analyzed using Mann Whitney test. The velopharyngeal competence in post-palatoplasty group consisted of 22.8% adequate result, 0.1% marginal result, and 68.1% inadequate result. Meanwhile, in the control group, there were 72.7% adequate and 27.3% inadequate competence. According to the result of the statistical test, this study concluded that there was a significant difference in speech outcome based on articulation pattern, hypernasality, speech intelligibility, and velopharyngeal distance between post-cleft palate closure patients and patients without cleft palate (p < 0.05). Majority of patients after cleft palate closure with two flaps pushback technique had inadequate velopharyngeal competence with moderate-severe hypernasality, severe nasal emission, abnormal speech intelligibility, and velopharyngeal distance ≥ 5.0 mm, whereas the majority of control group had an adequate velopharyngeal competence.